Assessing the moderating role of geopolitical risk in the nexus between ESG performance and stock price crash risk: a GMM approach - Agustin, Isnaini Nuzula; Tan, Michelle; Marheni, Dewi Khornida (Journal of Accounting and Investment, 2025)
Research aims: Amid rising global geopolitical upheaval, geopolitical risks progressively influence market volatility, particularly in Indonesia. This study examined the relationship between sustainable performance and stock price crash risk (SPCR), with geopolitical risk as a moderating variable.Design/Methodology/Approach: Data were collected from companies with environment, social, and governance (ESG) scores in the Refinitiv database over 2019-2023, resulting in 236 observations. Data analysis was conducted using the system generalized method of moments (GMM) approach, effectively addressing small sample size and endogeneity.Research findings: ESG performance imposed a negative and significant impact on SPCR. Furthermore, integrating ESG and geopolitical risk could reduce a stock market crash risk. A robustness test using coarsened exact matching provided consistency in these results.Theoretical contribution/Originality: This study introduces geopolitical risk as a moderating variable in the ESG-SPCR relationship, an area underexplored in current literature, particularly within Indonesia’s stock market. The results support the buffering hypothesis, reinforcing the need to incorporate geopolitical risk assessment while mitigating market crashes through ESG practices.Practitioner/Policy implication: Insights from this study guide policymakers and investors in mitigating market risks by integrating ESG performance and geopolitical risk assessment, particularly in environmental management,Research limitation/Implication: Reliance on a single ESG rating source may limit generalizability. Future research should incorporate multisource databases to capture measurement divergence.